Adapting Internal Audit Functions to the COVID-19 Pandemic: Evidence from the United Arab Emirates - Saeed, Omar; Amjad, Mohammed; ElKelish, Walaa Wahid; Miniaoui, Hela; El-Bannany, Magdi; AlShurideh, Muhammad; Lasyoud, Alhashmi Aboubaker (International Review of Management and Marketing, 2026)
This paper explores how the COVID-19 pandemic impacts the internal audit functions in the emerging market of the United Arab Emirates (UAE). This paper adopted an exploratory study using a qualitative approach. We used semi-structured, in-depth interviews to achieve the study objectives. The primary data collected was analyzed manually using thematic content analysis. The findings show that COVID-19 disrupted internal audit efficiency and productivity in the UAE due to limited physical access and remote work challenges. Audit quality varied, improving in firms with strong risk frameworks but declining where oversight weakened. Planning remained stable while fieldwork and communication processes shifted online. Information technology (IT) skills improved significantly, driven by digital audit requirements. Critical thinking and time management were tested, with mixed outcomes across firms. This paper helps to understand and focus on how the internal audit practices were affected by COVID-19. Also, it allows us to know how to deal with a similar situation in the future and to improve the internal audit profession.